As If It Weren't Hard Enough Already: Breaking down Hiring Discrimination Following Burnout - Philippe Sterkens; Stijn Baert; Claudia Rooman; Eva Derous (Institute of Labor Economics (IZA), 2020)
Hiring discrimination towards (former) burnout patients has been extensively documented in the literature. To tackle this problem, it is important to understand the underlying mechanisms of such discrimination. Therefore, we conducted a vignette experiment with 425 genuine recruiters and jointly tested the potential stigma against job candidates with a history of burnout that were mentioned earlier in the literature. We found candidates revealing a history of burnout elicit perceptions of requiring work adaptations, likely having more unpleasant collaborations with others as well as diminished health, autonomy, ability to work under pressure, leadership capacity, manageability, and learning ability, when compared to candidates with a comparable gap in working history due to physical injury. Led by perceptions of a reduced ability to work under pressure, the tested perceptions jointly explained over 90% of the effect of revealing burnout on the probability of being invited to a job interview. In addition, the negative effect on interview probability of revealing burnout was stronger when the job vacancy required higher stress tolerance. In contrast, the negative impact of revealing burnout on interview probability appeared weaker when recruiters were women and when recruiters had previously had personal encounters with burnout.
Keywords: J71; I14; C83; C91; 330; hiring discrimination; burnout; statistical discrimination; taste-based discrimination